STUDY OF FISHING SEASON FOR MANDAH FISHERMAN , INDRAGIRI HILIR DISTRICT, RIAU - Rizal Mualif; Bustari Bustari; Usman Usman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTMandah, Indaragiri Hilir Riau is an area that has potential in the field of fisheries, so information is needed to support management wisely so as not to damage the sustainability of fish resources, one of the supporting factors for fishing and fish resource management is spatial data and information available. and temporal, but it is very unfortunate that information on spatial and temporal distribution of fish species in Indonesia has not been well structured and systematically so that fishermen generally make arrests based on their ancestors' experiences or traditions who have high risks and opportunities for uncertainty. This study examines the pattern of fishing season in the Mandah waters of Indragiri Hilir Regency using data on monthly fishing production from 2009-2017 with results. The fishing season in Mandah District occurs from April to September with the peak fishing season in June and October until March is not the fishing season.Keywords: Mandah, Seasonal pattern, spatial, temporal